2011
DOI: 10.1016/j.pepi.2011.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous acoustic emissions monitoring and synchrotron X-ray diffraction at high pressure and temperature: Calibration and application to serpentinite dehydration

Abstract: International audienceWe have successfully developed an experimental setup that allows collecting in situ X-ray powder diffraction and simultaneously recording full waveform acoustic emissions (AE) at high pressure and temperature (PT) in a DIA multi-anvil device. This setup is a powerful tool for investigating rock embrittlement at high PT due to phase transitions and/or mineral reactions since both reaction progress (and kinetics) and AE triggering can be simultaneously monitored. The dehydration of natural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 50 publications
4
34
0
1
Order By: Relevance
“…Localization of deformation and dynamic faulting was not observed during the dehydration test performed at constant differential stress, which is consistent with recent experiments on serpentinite [ Rutter et al , 2009; Chernak and Hirth , 2010; Gasc et al , 2011]. However, the substantial compaction (up to 10%) observed during the dehydration reaction indicates the high deformability of dehydrating rocks.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Localization of deformation and dynamic faulting was not observed during the dehydration test performed at constant differential stress, which is consistent with recent experiments on serpentinite [ Rutter et al , 2009; Chernak and Hirth , 2010; Gasc et al , 2011]. However, the substantial compaction (up to 10%) observed during the dehydration reaction indicates the high deformability of dehydrating rocks.…”
Section: Resultssupporting
confidence: 90%
“…Two challenging problems encountered in addressing the possible importance of dehydration embrittlement in subduction are (1) the identification of dehydrating rocks within the subducting slab, for instance using seismic tomography, and (2) the understanding of the controlling factors promoting a macroscopic “embrittlement.” In particular, it is still unclear if dehydration reaction can induce strain localization and shear instabilities during deformation [ Hirose et al , 2006; Chernak and Hirth , 2010; Gasc et al , 2011]. …”
Section: Introductionmentioning
confidence: 99%
“…They showed that unstable fault behavior did not develop in the specimens, but rather that slow slip events took place. Compression experiments of antigoriterich serpentinite by Gasc et al (2011), who used a newly developed experimental setup that allows simultaneous collection of in situ X-ray diffraction data and recording of the full waveforms of acoustic emissions with a multianvil device, showed that the serpentinite samples did not produce detectable acoustic waves over the course of their dehydration. Proctor and Hirth (2015) conducted deformation tests with a new experimental method to vary the pore fluid pressure.…”
Section: Genesis Of Intermediate-depth Intraslab Earthquakesmentioning
confidence: 99%
“…In recent years, AE detection technology has been used in rock mechanics by many scholars [20][21][22][23][24][25][26][27]. For example, Ganne et al [20] studied the brittleness of rock before peak stress by the AE technique, and four stages of accumulated AE energy were given.…”
Section: Introductionmentioning
confidence: 99%
“…He et al [22] observed that there were much higher amplitude and lower frequency events near the bursting failure of rock samples, and the accumulated AE energy release increased rapidly from unloading state to rock failure. Gasc et al [23] studied rock structural transformation and mineral reaction under high temperatures and high pressures by X-ray diffraction and AE detection of serpentine. Chmel et al [24] studied AE energy release of granite under impact loading.…”
Section: Introductionmentioning
confidence: 99%